ANALYZING THE EFFECTS OF SOCIAL SECURITY REFORMS ON THE LIVELIHOODS AND GENERAL WELL-BEING OF UZBEKISTAN'S VULNERABLE COMMUNITIES - Abdullayev Suyun Artikovich (Modern American Journals, 2025)
This research paper aims to examine the impact of social security reforms on the well-being and livelihoods of vulnerable populations in Uzbekistan. The study focuses on understanding the effectiveness and outcomes of recent social security reforms implemented in the country, with a specific emphasis on their implications for vulnerable groups. By analyzing the changes in social security policies and their impact on the well-being and livelihoods of vulnerable populations, this research seeks to provide insights and recommendations for improving the social protection system in Uzbekistan.